The Paradox of Foreign Investment in Support Economic Sustainability After the Job Creation Law - Nafis Dwi Kartiko; Samuel Putra Soegiono; Carissa Amanda Siswanto (IHSA Institute, 2023)
The Job Creation Law and the Job Creation Perpu have substantially the same objectives and arrangements with the aim of optimizing the investment ecosystem amid global economic pressures and supporting sustainable economic growth. Simplification of investment requirements is key in this regulation, intended to invite more investment to Indonesia. However, the implementation of this law has raised various views and controversies regarding its impact on economic sustainability after the Job Creation Law. This study is designed to evaluate the impact of foreign investment on economic sustainability, in line with the ideals and objectives contained in the Job Creation Law. This research uses normative juridical with a qualitative descriptive approach. The result of this study is that it is necessary to balance economic growth with legislative integrity and inclusivity in the process of formulating Foreign Direct Investment policies